PERKEMBANGAN STUDI PEREMPUAN, KRITIK, DAN GAGASAN SEBUAH PERSPEKTIF UNTUK STUDI GENDER KE DEPAN - Marhaeni, A. A. I. N. (PIRAMIDA; Vol. 4, No. 2 Desember 2008, 2012)
The efforts to improve gender equity and equality have been taken place for yearssince the struggle of R.A. Kartini. Up to present, the efforts are still in place, however, notyet gain expected results. Preservation of gender inequality can be reproduced in family,society, as well as in the country.The increasing attention to gender is forced by women conference conducted by theUN. Four paradigms are identified: 1) Women in Develoment (WID) concept thatemerging researches on womwn participation in development process; 2) Gender andDevelopment (GAD) concept in which female is related to male; 3) Women’sempowerment; 4) Gender Mainstreaming. All of these paradigms have been implemented,but the results are not as expected.This condition reflects the needs of more critical attention in the implementation.For instances by considering women heterogeneity in terms of culture, social, andeconomis values, and thus it is necessary to take a need assessment in individual andinstitution levels. Men are also needed to take participation in gender studies to avoid bias.It ia also important to carry out program of education information communication tospread the information about women programs that have been and will be conducted toimprove women participation. Also, government commitment is crucial to increase gendersensitivity in public bureaucracy
Keywords: equality, equity, gender, development.